In-Office Bleaching in Tetracycline Stained Teeth: A Case Study - Bashar, AKM; Afsar, BR; Alam, MS (Bangladesh Medical Journal, 2009)
The aim of the study was to evaluate the efficacy of In-office bleaching protocol in tetracycline stained teeth. Discolored dentition diagnosed as homogenous dark brown tetracycline stained teeth was treated with in office bleaching protocol. Desired bleaching has achieved after six sessions of In-office bleaching protocol and satisfactory whitening was apparent throughout the postoperative two-year observation period. DOI: 10.3329/bmj.v36i2.3613 Bangladesh Medical Journal 36(2) 2007 52-55